2012
DOI: 10.1177/1742715012441876
|View full text |Cite
|
Sign up to set email alerts
|

The cultural dimensions of Italian leadership: Power distance, uncertainty avoidance and masculinity from an American perspective

Abstract: This article provides a cultural analysis of Italian leadership from a cross-cultural perspective. Americans view Italian leaders with cultural lenses and stereotypes often exaggerated by the media. Effective cross-cultural, business and international relations with Italians and Italian descendants require awareness of the true cultural dimensions beyond stereotypes and media portraits. Through the examination of Geert Hofstede's cultural dimensions and the Global Leadership and Organizational Behavior Effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…Cultural, and particularly religious, values appear to explain another finding: the fear that, by having a compassionate approach, managers will be perceived as weak, and would lose their authority and professionalism. Italy, Poland, Spain, and Colombia are countries with predominant Christian Catholic values, which influence the cultural values at personal and societal levels (Tavanti 2012). In these countries, compassion was conceived in terms of pity, associated to an emotional weakness that can lead to loss of power, impartiality, fairness, distance and control.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural, and particularly religious, values appear to explain another finding: the fear that, by having a compassionate approach, managers will be perceived as weak, and would lose their authority and professionalism. Italy, Poland, Spain, and Colombia are countries with predominant Christian Catholic values, which influence the cultural values at personal and societal levels (Tavanti 2012). In these countries, compassion was conceived in terms of pity, associated to an emotional weakness that can lead to loss of power, impartiality, fairness, distance and control.…”
Section: Discussionmentioning
confidence: 99%
“…Subordinates in high power distance cultures that fear expressing disagreement to the boss will be less likely to take initiative. The power distance index (PDI) influences which style of leadership is tolerated or expected by both managers and employees (Tavanti 2012), which in turn affects engagement in decision-making. Chiaburu et al (2015) found that PDI influences organizational citizenship behavior, namely, the extent to which employees show engagement and commitment beyond their ordinary tasks.…”
Section: Power Distance and Organizational Resiliencementioning
confidence: 99%
“…The gender dimension of masculinity vs. femininity refers to values beyond absolute gender difference. These values are related to masculine or feminine roles in a society (Hofstede et al 2010;Tavanti 2012). Masculinity is characterized by values like assertiveness, competition, performance, and focus on material success, while feminine values include maintaining relationships, solidarity, service orientation, and quality of life issues (Luczak et al 2010;Taras et al 2012;Tavanti 2012).…”
Section: Masculinity Vs Femininity and Organizational Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Cohen and Federico (2001) define Italy as one of the world's richest and economically advanced countries due to the fact that small Italian firms benefited from unique social interactions resulting from shared values and belief systems. Italy is associated with other countries that tolerate more power distance (Tavanti 2012). While Italians accept and somehow expect that some groups in society will be more powerful than others, they often express cynicism about persons in positions of authority, generally supporting the breaking of petty rules, ridiculing authority or people in positions of power (Flower and Falassi 2006).…”
Section: National Culture and Workmentioning
confidence: 99%